Vitamin K-antagonists accelerate atherosclerotic calcification and induce a vulnerable plaque phenotype. - Leon J Schurgers; Ivo A Joosen; Eduard M Laufer; Martijn L L Chatrou; Marjolein Herfs; Mark H M Winkens; Ralf Westenfeld; Verena Veulemans; Thilo Krueger; Catherine M Shanahan; Willi Jahnen-Dechent; Erik Biessen; et al. (PLoS ONE)
Background Vitamin K-antagonists (VKA) are treatment of choice and standard care for patients with venous thrombosis and thromboembolic risk. In experimental animal models as well as humans, VKA have been shown to promote medial elastocalcinosis. As vascular calcification is considered an independent risk factor for plaque instability, we here investigated the effect of VKA on coronary calcification in patients and on calcification of atherosclerotic plaques in the ApoE(-/-) model of atherosclerosis. Methodology/principal findings A total of 266 patients (133 VKA users and 133 gender and Framingham Risk Score matched non-VKA users) underwent 64-slice MDCT to assess the degree of coronary artery disease (CAD). VKA-users developed significantly more calcified coronary plaques as compared to non-VKA users. ApoE(-/-) mice (10 weeks) received a Western type diet (WTD) for 12 weeks, after which mice were fed a WTD supplemented with vitamin K(1) (VK(1), 1.5 mg/g) or vitamin K(1) and warfarin (VK(1)&W; 1.5 mg/g & 3.0 mg/g) for 1 or 4 weeks, after which mice were sacrificed. Warfarin significantly increased frequency and extent of vascular calcification. Also, plaque calcification comprised microcalcification of the intimal layer. Furthermore, warfarin treatment decreased plaque expression of calcification regulatory protein carboxylated matrix Gla-protein, increased apoptosis and, surprisingly outward plaque remodeling, without affecting overall plaque burden. Conclusions/significance VKA use is associated with coronary artery plaque calcification in patients with suspected CAD and causes changes in plaque morphology with features of plaque vulnerability in ApoE(-/-) mice. Our findings underscore the need for alternative anticoagulants that do not interfere with the vitamin K cycle.